EFEKTIVITAS PENGELOLAAN DANA DESA DALAM MENINGKATKAN PEMBANGUNAN DESA MENURUT PERSPEKTIF EKONOMI ISLAM (STUDI KASUS DESA SIJABUT TERATAI KECAMATAN AIR BATU KABUPATEN ASAHAN) - Nurbaiti; Nursantri Yanti; Trisnawati (EKSYA : Jurnal Ekonomi Syariah, 2022)
This study aims to determine the effectiveness of village fund management in improving village development, inhibiting factors in village development, and village development in an Islamic economic perspective. The research methodology used is qualitative research. Data collection techniques with the method of observation, interviews, and documentation. The results of this study are the Effectiveness of Village Fund Management in Sijabut Teratai village of 80.87%, including in the category of quite effective. Factors that hinder the effectiveness of village fund management in improving village development include land acquisition for residents, electricity poles, large trees and weather constraints. The effectiveness of village fund management in improving village development according to an Islamic economic perspective has five foundations for Islamic development. Islamic development describes five foundations, namely monotheism, caliphate, justice, tazkiyyah and al-falah. Village development is closely related to Islamic economics which can be linked to monotheism, namely the development carried out aimed at meeting the needs of the village community to assist the community in carrying out activities. The caliphate is closely related to the development carried out by the village with the aim of community welfare including the human function as caliph. Justice is closely related to development, namely the development carried out in the village of Sijabut Teratai does not only focus on one hamlet, but in every hamlet. Tazkiyyah relates to the development carried out by the village as the responsibility of the village government which has been given a mandate by the central government. And Al-Falah relates to the success that has been achieved by the village because it has succeeded in carrying out development that leads to community welfare.